2016
DOI: 10.1371/journal.pone.0168772
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Role of Mast Cells in Cystitis-Associated Lower Urinary Tract Dysfunction: A Multidisciplinary Approach to the Study of Chronic Pelvic Pain Research Network Animal Model Study

Abstract: Bladder inflammation frequently causes cystitis pain and lower urinary tract dysfunction (LUTD) such as urinary frequency and urgency. Although mast cells have been identified to play a critical role in bladder inflammation and pain, the role of mast cells in cystitis-associated LUTD has not been demonstrated. Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic and debilitating inflammatory condition of the urinary bladder characterized by the hallmark symptoms of pelvic pain and LUTD. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
2
41
0
4
Order By: Relevance
“…In fact, the elevated number of mast cells in the bladder tissue in case of inflammation induces mast cells degranulation and release of their pre-formed mediators. In light of other reports and according to our experiment during the course of FIC, MC increasingly releases TNF-in the blood which up-regulates by its role the expression of VEGF-A (Wang et al, 2016b) and because of hypoxia induced by inflammation, VEGF-A was up-regulated to induce vasodilation, hyper-vascularity and glomerations at the site of inflammation (Ramakrishnan et al, 2014). This explains the significant increase in the VEGF-A immunohistochemical staining which was highly distributed in urolithium and sub-urolithial layers of the affected cats.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, the elevated number of mast cells in the bladder tissue in case of inflammation induces mast cells degranulation and release of their pre-formed mediators. In light of other reports and according to our experiment during the course of FIC, MC increasingly releases TNF-in the blood which up-regulates by its role the expression of VEGF-A (Wang et al, 2016b) and because of hypoxia induced by inflammation, VEGF-A was up-regulated to induce vasodilation, hyper-vascularity and glomerations at the site of inflammation (Ramakrishnan et al, 2014). This explains the significant increase in the VEGF-A immunohistochemical staining which was highly distributed in urolithium and sub-urolithial layers of the affected cats.…”
Section: Discussionsupporting
confidence: 77%
“…Although some studies suggested that the presence of mast cells in the detrusor muscle is quite specific of IC, 10,11 other data suggest that this cannot be confirmed. 12,13 Article The importance of an early diagnosis for predicting the clinical evolution of the disease and the development of associated diseases of other organs or body sites has not yet been properly investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Some clinicians now consider that many of the pathological features usually described are non-specific. [9][10][11] However, intrafascicular fibrosis, an increase in the number of mast cells in the detrusor, denudation of urothelium in patients with a diagnosis of with BPS/IC are observations described in many studies. 11 There are conflicting data on the usefulness of mast cell count to diagnose IC.…”
Section: Introductionmentioning
confidence: 99%
“…The data of histopathology of the bladder revealed the role of cell-mediated immunity in IC/BPS, which does not exclude the possibility that autoimmune inflammation is probably a component of pathophysiology in patients with this disease (7). Although mast cells are characteristic features of this disease, there is no consensus on their specificity and diagnostic significance.…”
Section: Introductionmentioning
confidence: 93%
“…Different degrees of severity of inflammation are detected in the biopsy specimens of the bladder; however, cellular mechanisms of inflammation in IC/BPS and the pro-cesses leading to tissue damage and fibrosis are not yet clear (6,7). Among many suggested causes, mast cell activation is noteworthy (8).…”
Section: Introductionmentioning
confidence: 99%